Malaysia's 14th general election and UMNO's fall : intra-elite feuding in the pursuit of power - Gomez, Edmund Terence; Mohamed Nawab; Case, William (London ; New York : Routledge, Taylor & Francis Group, 2019)
'The 2018 Malaysian General Election will stand as a major defining event in Malaysian history, when the ruling Barisan Nasional coalition unexpectedly lost power in the country they had ruled for over half a century. This volume brings together scholars who assess one fundamental factor that brought about this game-changing event in Malaysian politics: intra-elite feuding in the leading Malay-based political parties. This study provides an analysis of individual state politics as well as national trends shaped by the actions of leaders in government and the opposition. An indispensable guide for scholars studying the politics of Malaysia and of Southeast Asia more broadly, it will be of great interest for all readers with an interest in Malaysian politics'--
Democratization in an age of authoritarianism : theorizing Malaysia's GE14 / William Case -- Elite contestations, politics of reform and new voting dynamics of peninsular states in GE14 / Johan Saravanamuttu -- Elite feuds, patronage and factions : UMNO's demise / Sri Murniati -- Electoral boundaries in Malaysia's 2018 election : malapportionment, gerrymandering and UMNO's fall / Kai Ostwald --'10 years under Pakistan is better than 50 years under UMNO/BN' : pre-electoral conflict and campaign rhetoric in Selangor / Elvin Ong -- A tale of intra-Malay elite feuds in Kuala Lumpur and Putrajaya / Prashant Waikar -- Gambling on grievances : Melaka in GE14 and after / Amalina Anuar and Chan Xin Ying -- Bangsa Johor : factions, feuds and fall of UMNO / Rashaad Ali -- Penang : victory by support or defeat by chance? / Chan Xin Ying -- The battle for Perak / Iskandar Dzulkarnai Ahmad Junid -- Parties versus personalities in Kedah politics : unstable and hung state assembly in Kedah's GE14 / Mohd. Azizuddin Mohd. Sani -- The green tsunami in Terengganu : the re-emergence of Parti Islam se-Malaysia / Wan Rohilla Ganti -- Intra-Islamist elite competition in Kelantan / Najwa Abdullah.
Includes bibliographical references and index.
Keywords: United Malays National Organisation; Barisan Nasional (Organization); Elections -- Malaysia; Elite (Social sciences) -- Political activity -- Malaysia; Malaysia -- Politics and government -- 21st century